Therapeutic possibilities in dentistry for the treatment of facial paralysis (Research, Society and Development, 2023)
Peripheral facial paralysis or Bell's palsy is characterized by injury or damage to the facial nerve that results in the loss of facial muscle movement, affecting the patient's quality of life through physical, psychological, social, aesthetic and functional disorders This research aimed to provide better knowledge and understanding about the disease, identifying therapeutic possibilities that can be used by dentistry professionals. As a data collection technique, an integrative bibliographic review was chosen, through searches in online databases, such as Google Scholar in Portuguese, the Scientific Electronic Library Online (SciELO), Portal de Periódicos CAPES/MEC and Latin American and Caribbean Literature (Lilacs). Next, the summary of the articles found was read to identify publications that did not meet the exclusion criteria. Finally, the articles were read in full, and the main information was used to construct this research. The results showed that there are several procedures that can be used by dentistry professionals in the treatment of peripheral facial paralysis, such as acupuncture, laser therapy, electrotherapy, support threads, hyaluronic acid and botulinum toxin, which applied alone or in combination, as a whole, they are capable of providing improvements in facial symmetry and functionality associated with patients' muscles, influencing the improvement of their self-esteem and quality of life.